(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2015)
Knowledge mobilization seeks to identify and support authentic research collaborations between community and university so that benefits of the research accrue to both partners. Knowledge brokering is a key knowledge mobilization mechanism that helps community and university partners connect and build relationships in order to share expertise for mutual opportunity. There remains a need to describe in detail the typical knowledge brokering devices and methodologies. This paper presents a detailed description of York Universityâ€™s knowledge brokering service which is based on eight years of knowledge mobilization practice. The process is broken into 5 broad stages: 1) in progress; 2) no match; 3) match and no activity; 4) match and activity; 5) match and project. Stage 5 includes a step to identify the non-academic impacts of the collaborative research project. This process is illustrated using examples from York Universityâ€™s practice in which a match was brokered for 82% of the 342 knowledge mobilization opportunities received between 2006-2014. York University partners with United Way York Region (UWYR) to create a regional approach to knowledge mobilization supports. This paper illustrates the impacts on community and university knowledge mobilization partners following the introduction of a community-based knowledge broker at UWYR. Â